2006
DOI: 10.1097/01.prs.0000219170.74059.94
|View full text |Cite
|
Sign up to set email alerts
|

V-Y Rotation Advancement Fasciocutaneous Flap for Excisional Defects of Pilonidal Sinus

Abstract: The authors believe that the V-Y rotation advancement flap is a good alternative method for the treatment of pilonidal sinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Oblique or asymmetric closure techniques such as the Karydakis flap and the Boscom procedure were based on this principle. 19 In our series, we experienced that the S-GAP flap efficiently flattens the intergluteal sulcus.…”
Section: Discussionmentioning
confidence: 95%
“…Oblique or asymmetric closure techniques such as the Karydakis flap and the Boscom procedure were based on this principle. 19 In our series, we experienced that the S-GAP flap efficiently flattens the intergluteal sulcus.…”
Section: Discussionmentioning
confidence: 95%
“…4 We observed that this flap did not affect the sensation of the gluteal region. With this study, we could generalize this finding to whole body because we have not seen any sensory impairment, pain, or numbness.…”
Section: Discussionmentioning
confidence: 95%
“…When we indicated the usefulness of this flap on sacral pilonidal sinus defects in our previous study, 4,5 we excluded those patients with sacral pilonidal sinus and fingertip amputation from this article. In this article, we would like to share our experience and the excellent results with V-Y rotation advancement flap on different parts of the body.…”
mentioning
confidence: 99%
“…In general, they lack soft tissue and skin to cover the defect. To solve this problem, we use V-Y rotation advancement flap, which is first described by Argamosa [3] and used by many surgeons [6,11,37], bilaterally in fingertip amputations. Rotation besides advancement makes this flap more mobile and easier to cover larger defects in all amputation planes.…”
Section: Introductionmentioning
confidence: 99%